2021
DOI: 10.3389/fonc.2021.685786
|View full text |Cite
|
Sign up to set email alerts
|

Major Differences in Lymphocyte Subpopulations Between Cerebrospinal Fluid and Peripheral Blood in Non-Hodgkin Lymphoma Without Leptomeningeal Involvement: Flow Cytometry Evidence of a Cerebral Lymphatic System

Abstract: Cerebrospinal fluid (CSF) flow cytometry has a crucial role in the diagnosis of leptomeningeal disease in onco-hematology. This report describes the flow cytometry characterization of 138 CSF samples from patients affected by non-Hodgkin lymphoma, negative for disease infiltration. The aim was to focus on the CSF non-neoplastic population, to compare the cellular composition of the CSF with paired peripheral blood samples and to document the feasibility of flow cytometry in hypocellular samples. Despite the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…The resultant potential panel of protein biomarkers is in agreement with a previous study by Iole Cordone et al [ 65 ]. In that study, the flow cytometry characterization of 138 CSF samples from patients suffering from non-Hodgkin lymphoma, and negative for leptomeningeal infiltration (LM−), showed that CSF is a tissue rich in CD2−, CD3− and CD5− positive T lymphocytes.…”
Section: Discussionsupporting
confidence: 91%
“…The resultant potential panel of protein biomarkers is in agreement with a previous study by Iole Cordone et al [ 65 ]. In that study, the flow cytometry characterization of 138 CSF samples from patients suffering from non-Hodgkin lymphoma, and negative for leptomeningeal infiltration (LM−), showed that CSF is a tissue rich in CD2−, CD3− and CD5− positive T lymphocytes.…”
Section: Discussionsupporting
confidence: 91%
“… EVs in lymphatic malignancies. Lymphoma is a hematological malignancy associated with the lymphatic system [ 174 , 175 ]. A growing body of evidence has indicated that EVs actively participate in the pathogenesis of various lymphomas [ 176 , 177 ].…”
Section: Evs In Cell-cell and Cell-extracellular Matrix Communication...mentioning
confidence: 99%